Sustainable Tall Green Building-Context Approaching Bangladesh - Ferdousi, Jannat Ara; Gupta, Bijoy Dash (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Bangladesh is a member of D-8 (Developing 8) countries in the world. But one of the problem is that it is a densely populated country. The population of this country has been increased at such a rate over the past few years that development plans for the country by the government of Bangladesh has undergone many tremendous transformations. Especially in the urban area is highly populated, but the amount of land is relatively very which has put severe pressure on the ecosystem of the urban life. The increased population has impacted the ecosystem of densely populated cities like Dhaka, Chittagong and Narayanganj. The changes in the population were paralleled by the real estate construction and housing industries. Dhaka, Chittagong, Narayanganj are some of the most polluted cities in Bangladesh. This is why sustainable green building-context is approaching Bangladesh.